2021
DOI: 10.3389/fpsyg.2021.574232
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Be Employable Through Volunteering: A Qualitative Study on the Development of Employability Capital of Young People

Abstract: Over the last decades, consistent research showed that voluntary work could be considered as a tool for professional development and concrete employment: volunteering could be either experienced as a desire to improve career opportunities or to acquire new skills. The study aimed to investigate voluntary work as a context of informal and non-formal workplace learning and vocational guidance, useful to develop skills and abilities, namely the capital of personal and social resources, that could promote future e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
5
0
2
Order By: Relevance
“…They not only educate learners but also empower them to become active and engaged citizens who can contribute to the development of their communities. Giancaspro and Manuti (2021) state that in the Philippines, ALS is a program that provides an alternative way of education to out-of-school youths and adults who have not completed their basic education. Their dedication, hard work, and commitment are critical in ensuring that the ALS program achieves its goals and improves the lives of those who are frequently left behind in the traditional educational system.…”
Section: Resultsmentioning
confidence: 99%
“…They not only educate learners but also empower them to become active and engaged citizens who can contribute to the development of their communities. Giancaspro and Manuti (2021) state that in the Philippines, ALS is a program that provides an alternative way of education to out-of-school youths and adults who have not completed their basic education. Their dedication, hard work, and commitment are critical in ensuring that the ALS program achieves its goals and improves the lives of those who are frequently left behind in the traditional educational system.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, I-O professionals who received training that included nonprofit consulting experiences may be better equipped to conduct I-O work that supports beneficial societal outcomes. Nevertheless, course-based nonprofit work can provide a similar experience to volunteer work that enhances I-O graduate trainee professional growth and facilitates tangible employment outcomes like enhancing career prospects or acquiring new skills (Giancaspro & Manuti, 2021). Just as engaging in volunteering provides individuals with a valuable opportunity to enhance their social and transferable skills, participate in informal and nonformal learning, and boost their employability (Kamerāde & Ellis Paine, 2014; Otero et al, 2007), so too can these experiences within graduate training benefit I-O students.…”
Section: How Nonprofit Organizations Can Support Studentsmentioning
confidence: 99%
“…There is a link between volunteering and career clarity, as volunteering can provide individuals with valuable opportunities to explore their interests, values, and skills in a real-world context (Giancaspro & Manuti, 2021). Volunteering allows individuals to gain new experiences, knowledge, and skills that can help them develop a clearer understanding of their career goals and aspirations.…”
Section: Career Clarity and Volunteer Experiencesmentioning
confidence: 99%
“…Volunteering can significantly impact career pathways and employability capital, which is especially important for those who lack a preexisting professional network or field experience (Giancaspro & Manuti, 2021). Borwein (2014) suggested that community-based volunteer experiences may be seen as important for entry-level positions at a time when less than 25% of employers are willing to consider job applicants with no related experience.…”
Section: Career Clarity and Volunteer Experiencesmentioning
confidence: 99%